Galectin-10, the protein that forms Charcot-Leyden crystals, is not stored in granules but resides in the peripheral cytoplasm of human eosinophils. Issue 1 (28th February 2020) - Melo, Rossana C N; Wang, Haibin; Silva, Thiago P; Imoto, Yoshimasa; Fujieda, Shigeharu; Fukuchi, Mineyo; Miyabe, Yui; Hirokawa, Makoto; Ueki, Shigeharu; Weller, Peter F
Abstract: A predominant protein of human eosinophils is galectin-10 (Gal-10), also known as Charcot-Leyden crystal protein (CLC-P) because of its remarkable ability to form Charcot-Leyden crystals (CLCs), which are frequently found in tissues from patients with eosinophilic disorders. CLC-P/Gal-10 is highly expressed in human eosinophils and considered a biomarker of eosinophil involvement in inflammation. However, the intracellular sites where large pools of CLC-P/Gal-10 constitutively reside are still unclear, and whether this protein is derived or not from eosinophil granules remains to be established. Here, we applied pre-embedding immunonanogold transmission electron microscopy combined with strategies for optimal antigen and cell preservation and quantitative imaging analysis to investigate, for the first time, the intracellular localization of CLC-P/Gal-10 at high resolution in resting and activated human eosinophils. We demonstrated that CLC-P/Gal-10 is mostly stored in the peripheral cytoplasm of human eosinophils, being accumulated within an area of ∼250 nm wide underneath the plasma membrane and not within specific (secretory) granules, a pattern also observed by immunofluorescence. High-resolution analysis of single cells revealed that CLC-P/Gal-10 interacts with the plasma membrane with immunoreactive microdomains of high CLC-P/Gal-10 density being found in ∼60% of the membrane area. Eosinophil stimulation with CCL11 or TNF-α, which are known inducers of eosinophil secretion, did not change the peripheral localization of CLC-P/Gal-10 as observed by both immunofluorescence and immuno-EM (electron microscopy). Thus, in contrast to other preformed eosinophil proteins, CLC-P/Gal-10 neither is stored within secretory granules nor exported through classical degranulation mechanisms (piecemeal degranulation and compound exocytosis). Graphical Abstract: Ascertains the intracellular sites of CLC-P/Gal-10 within resting and activated human eosinophils, revealing preformed stores associated with the peripheral cytosol and plasma membrane and not with granules. .